ORACULAR DIVINATION AS A MODE OF EXISTENTIAL INFORMATION GATHERING IN URHOBOLAND IN DELTA STATE, NIGERIA - AKPOMUVIE, Orhioghene Benedict (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
In this article, attitudinal problems associated with the acceptance and reliance on oracular divination as a vehicle for looking into the future for what life holds for the individuals and groups was discussed. Apart from stating the relevance of this source of information on the life-course, the article also addressed the threats posed to it by globalization, open hostility and gross misunderstanding of the practice. The research which was conducted in the twenty three (23) polities of Urhoboland, showed very significant patronage given to divination. It further showed that during crises, the people in the study area are compelled to seek the intervention of God and the cult of ancestors to identify the sources of the tension and restore order through divination. In addition, the Urhobo traditionalists are reluctant to engage in any human endeavor without seeking the face of God and the ancestors for guidance and intervention. The researcher however observed that as the research progressed, it became obvious that most eminent personalities, who participated in the study and patronized diviners, became wary of my presence for fear of knowing how they coped with life challenges. The study recommended that some aspects of divination should be incorporated into our tertiary school curriculum particularly in the (department of traditional medicine) as well as the registration of genuine practitioners by the Traditional Medicine Boards of each State of the federation.